2019
DOI: 10.1038/s42003-018-0266-5
|View full text |Cite
|
Sign up to set email alerts
|

Field metabolic rates of teleost fishes are recorded in otolith carbonate

Abstract: Field metabolic rate (FMR) is key to understanding individual and population-level responses to environmental changes, but is challenging to measure in field conditions, particularly in aquatic environments. Here we show that FMR can be estimated directly from the isotopic composition of carbon in fish otoliths (δ13Coto). We describe the relationship between δ13Coto values and oxygen consumption rate, and report results from laboratory experiments relating individual-level measurements of oxygen consumption ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(138 citation statements)
references
References 67 publications
4
134
0
Order By: Relevance
“…In reality, activity scope may vary depending on life history traits and behavior (Killen, Norin, & Halsey, 2017), and field metabolic rates can be elevated with the presence of predators, which in turn can affect nutrient cycling (Dalton, Tracy, Hairston, & Flecker, 2018;Guariento et al, 2018). Refining established techniques, such as bio-telemetry (Norin & Clark, 2016) or otolith chemistry (Chung, Trueman, Godiksen, Holmstrup, & Grønkjaer, 2019) may improve estimates of field metabolic rates. Similarly, specific dynamic action (SDA), which is the metabolic rate needed to assimilate food (Hou et al, 2008) depends on the quality and quantity of food (McCue, 2006) (Casey et al, 2019) or compound-specific stable isotope analyses (Hopkins & Ferguson, 2012) permit improved insights into species-specific ingestion of prey resources.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, activity scope may vary depending on life history traits and behavior (Killen, Norin, & Halsey, 2017), and field metabolic rates can be elevated with the presence of predators, which in turn can affect nutrient cycling (Dalton, Tracy, Hairston, & Flecker, 2018;Guariento et al, 2018). Refining established techniques, such as bio-telemetry (Norin & Clark, 2016) or otolith chemistry (Chung, Trueman, Godiksen, Holmstrup, & Grønkjaer, 2019) may improve estimates of field metabolic rates. Similarly, specific dynamic action (SDA), which is the metabolic rate needed to assimilate food (Hou et al, 2008) depends on the quality and quantity of food (McCue, 2006) (Casey et al, 2019) or compound-specific stable isotope analyses (Hopkins & Ferguson, 2012) permit improved insights into species-specific ingestion of prey resources.…”
Section: Discussionmentioning
confidence: 99%
“…2). Considering that the M oto term is constrained by both upper (,0.5) (Table 1) and lower boundaries (0), this may imply that the relationship is not a simple linear regression (Kalish 1991a), but an exponential decay model in increasing form (Chung et al 2019). It is critical that the relationship between M oto values and oxygen consumption should be widely investigated, especially across species.…”
Section: Relationship Between M Oto and Oxygen Consumptionmentioning
confidence: 99%
“…com/products/rstudio/; Wright, 2012, Team, 2014). The relationships between δ 13 C and SMR, MMR and AAS were modelled as a logarithmic relationship (Kalish, 1991a;Chung et al, 2019b):…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Field studies have also revealed that δ 13 C relates to measures of swimming capacity (Sherwood and Rose, 2003), temperature-driven metabolic cycles (Wurster and Patterson, 2003) and ontogenetic reductions in mass-specific metabolic rate (Trueman et al, 2016;Wurster and Patterson, 2003). To date, only one study has directly related δ 13 C in otoliths to measures of metabolic rate, uncovering a significant negative relationship between δ 13 C and standard metabolic rate (SMR) in Atlantic cod (Chung et al, 2019b). Consequently, a gap exists in understanding how δ 13 C relates to other metabolic parameters.…”
Section: Introductionmentioning
confidence: 99%